Artificial Intelligence and Economic Growth; Sustainable Development Challenges in Muslim World - Shahzad, Shakeel; Ahmed Khan, Saud; Waheed, Taraq (IKONOMIKA, 2025)
While the world rushes to implement Artificial Intelligence (AI), there are some concerns that arise. AI has the capability to have an impact on economic expansion and the employment sector. The influence is assumed to be substantial, since increased productivity and lowered wages and prices combined with a high level of automation implies labor substitution. The widespread adoption of artificial intelligence has the potential to impact the global economy and specifically the Muslim world countries drastically. We studied the influence of AI over economic growth using mathematics, emphasizing the fact that AI is unlike any other production factor. Moreover, the study modified the production function as per the axioms of correct specification of the model and according the current situations. We have established AI's potential impacts on the economic growth. Nations with lower workforce ratios are expected to shift towards technology that increases labor productivity. On the other hand, capital productivity increasing technology can be used by nations grappling with the problems of an aging population. Care must be taken in determining the optimal deployment of models.